Reagentless iron detection in water based on unclad fiber optical sensor - Nurul Atika Nabila Jaharudin; Noran Azizan Cholan; Nurfatihah Che Abd Rashid; Nazrah Ilyana Sulaiman; Kim Gaik Tay; Nor Hafizah Ngajikin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
A simple and low-cost fiber based optical sensor for iron detection is demonstrated in this paper. The sensor head consist of an unclad optical fiber with the unclad length of 1 cm and it has a straight structure. Results obtained shows a linear relationship between the output light intensity and iron concentration, illustrating the functionality of this iron optical sensor. Based on the experimental results, the sensitivity and linearity are achieved at 0.0328/ppm and 0.9824 respectively at the wavelength of 690 nm. With the same wavelength, other performance parameters are also studied. Resolution and limit of detection (LOD) are found to be 0.3049 ppm and 0.0755 ppm correspondingly. This iron sensor is advantageous in that it does not require any reagent for detection, enabling it to be simpler and cost-effective in the implementation of the iron sensing.